An efficient and robust approach to predict ship self-propulsion coefficients. (November 2019) - Villa, Diego; Gaggero, Stefano; Gaggero, Tomaso; Tani, Giorgio; Vernengo, Giuliano; Viviani, Michele
Abstract: Achieving a reliable and accurate numerical prediction of the self-propulsion performance of a ship is still an open problem that poses some relevant issues. Several CFD methods, ranging from boundary element methods (BEM) to higher-fidelity viscous Reynolds averaged Navier–Stokes (RANS) based solvers, can be used to accurately analyze the separate problems, i.e. the open water propeller and the hull calm water resistance. However, when the fully-coupled self-propulsion problem is considered, i.e. the hull advancing at uniform speed propelled by its own propulsion system, several complexities rise up. Typical flow simplifications adopted to speed-up the simulations of the single analysis (hull and propeller separately) lose their validity requiring a more complex solver to tackle the fully-coupled problem. The complexity rises up further when considering a maneuver condition. This aspect increases the computational burden and, consequently, the required time which becomes prohibitive in a preliminary ship design stage. The majority of the simplified methods proposed in literature to include propeller effects, without directly solve the propeller flow, in a high-fidelity viscous solver are not able to provide all the commonly required self-propulsion coefficients. In this work, a new method to enrich the results from a body force based approach is proposed and investigated, with the aim to reduce as much as possible the computational burden without losing any useful result. This procedure is tested for validation on the KCS hull form in self-propulsion and maneuver conditions.